Effects of physical activity and sedentary behaviors on cardiovascular disease and the risk of all-cause mortality in overweight or obese middle-aged and older adults - Yongqiang Zhang; Xia Liu (Frontiers in Public Health, 2024)
AimThe aim of this study was to respectively explore the relationships between physical activity and sedentary behaviors and cardiovascular disease (CVD) and all-cause mortality risk in overweight/obese middle-aged and older patients, and also assess the interaction between physical activity and sedentary behaviors.MethodsData of middle-aged and older adults with body mass index (BMI) ≥25 kg/m2 were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2007–2018 in this retrospective cohort study. Weighted univariate and multivariate logistic regression analyses were used to explore the associations between physical activity and sedentary behaviors and CVDs; weighted univariate and multivariate Cox regression analyses were used to explore the relationships between physical activity and sedentary behaviors with the risk of all-cause mortality. The interaction effect between physical activity and sedentary behaviors on CVD and all-cause mortality was also assessed. We further explored this interaction effect in subgroups of age and BMI. The evaluation indexes were odds ratios (ORs), hazard ratios (HRs), and 95% confidence intervals (CIs).ResultsAmong 13,699 eligible patients, 1,947 had CVD, and 1,560 died from all-cause mortality. After adjusting for covariates, patients who had high sedentary time seemed to have both high odds of CVD [OR = 1.24, 95% CI: (1.06–1.44)] and a high risk of all-cause mortality [HR = 1.20, 95% CI: (1.06–1.37)]. Furthermore, being insufficiently active was linked to high odds of CVD [OR = 1.24, 95% CI: (1.05–1.46)] as well as a high risk of all-cause mortality [HR = 1.32, 95% CI: (1.15–1.51)]. High sedentary time and being insufficiently active had an interaction effect on both high odds of CVD [OR = 1.44, 95% CI: (1.20–1.73)] and high risk of all-cause mortality [HR = 1.48, 95% CI: (1.24–1.76)]. Individuals of different ages with/without obesity need to focus on the potential CVD/mortality risk of high sedentary time and low physical activity (all P < 0.05).ConclusionReducing sedentary time combined with increasing physical activity may benefit health by reducing both the risk of CVD and all-cause mortality in overweight or obese middle-aged and older adults.